Areal summed corneal power shift is an important determinant for axial length elongation in myopic children treated with overnight orthokeratology. Issue 11 (31st January 2019) - Hu, Yin; Wen, Canhong; Li, Zhouyue; Zhao, Wenchen; Ding, Xiaohu; Yang, Xiao
Abstract : Background: The myopia control effect of orthokeratology (OK) varies among individuals. The variation might relate to the proposed 'areal summation effect' of lens-induced visual signals. The current study evaluated the areal summed corneal power shift (ASCPS) in myopic children treated with OK lenses and assessed whether the ASCPS achieved at early post-OK visit can predict the lens long-term effect on the axial length (AL) elongation. Methods: Study participants were 130 myopic children treated with OK lenses (age range, 8 to 15 years) in a prospective study. Corneal topography and AL were measured at baseline and 1, 3, 6, 9 and 12 months after OK lens wear. The ASCPS was derived from corneal topographic measurements and defined as the change in the areal summed corneal relative refraction at the follow-up visit from baseline. The impact of the ASCPS achieved at the 1 month post-OK visit on the 12 months AL elongation was examined using multivariate linear regression analysis. Results: Baseline age of the study participants was 11.8 ± 1.8 years and their mean spherical equivalent was −3.00±0.92 D. The ASCPS was 6.90±6.09 D*mm at the 1 month visit and remained stable throughout the follow-up period (p=0.5508, repeated-measures analysis of variance). Greater 1 month ASCPS was associated with slower AL elongation at the 12 months visit (β=−0.007, p=0.001). Conclusions: The ASCPS achieved at early post-OK visit is predictive for the lens long-term effect on the myopic AL elongation. The parameter is potential in guiding the OK lens practice to slow down axial growth in myopic children.